New halogenated flame retardants in the atmosphere of nine urban areas in China: Pollution characteristics, source analysis and variation trends. (May 2017) - Li, Qilu; Yang, Kong; Li, Kechang; Liu, Xin; Chen, Duohong; Li, Jun; Zhang, Gan
Abstract: Since the ban of polybrominated diphenyl ethers (PBDEs) excluding deca-BDE in China, new halogenated flame retardants (NHFRs), such as new brominated flame retardants and Dechlorane Plus, have become widely used. In this study, we assessed the atmospheric gaseous and particulate levels of eight NHFRs in nine urban areas in China. We detected high mean atmospheric (vapour plus particle phases) concentrations of tetrabromophthalate (TBPH) (74.8 pg m −3 ) and decabromodiphenyl ethane (DBDPE) (68.8 pg m −3 ), two major NHFRs. Most of the gaseous and particulate NHFR concentrations presented seasonal variations (from summer to autumn), possibly driven by temperature. Spatially, concentrations and patterns of the NHFRs differed among the nine cities. Significantly higher concentrations were detected in cities with higher gross domestic products. The composition, especially the DBDPE/TBPH ratio ( S ), were clearly different among the cities, which pattern in each city are likely driven by variations in the type of industries operating in each city. Based on the temporal analysis of other researches and our data, PBDE levels have decreased markedly, while NHFRs levels have increased. Since high NHFR levels had detrimental effects on public health, NHFRs research warrants more attention. Graphical abstract: Highlights: Eight NHFRs were analyzed in vapour and particle phase from nine cities in China. High DBDPE and TBPH levels were detected in particle and vapour phases, respectively. Industries involved to FRs may contribute high NHFR concentrations. An interesting pattern was found from the compositions of NHFRs in nine cities. NHFR concentrations presented an increasing trend in recent years in China. Abstract : New halogenated flame retardant levels in air of China have increased, and spatial distributions of NHFRs were influenced by GDP and industrial structures.